The Somali Conflict: A Detailed Analysis of its Causes and Factors (Global Journal of Human-Social Science, 2021)
The state of Somalia has been plagued with internal disputes since its independence The use of clans and ethnic groups contributed to the rise of conflict in the country However several factors have contributed to the civil war and the ongoing conflict in the country This paper analyses the different factors of conflict present in Somalia since the grant of independence This paper does not address the history of Somalia except when it relates to the war But it looks at the causal and contributing factors of the conflict and how it led to an escalated war In analysing this conflict this paper adopts the Bloomfield and Moulton model of conflict and Edward Azar s theory of Protracted Social Conflict
Keywords: conflict; somalia; civil war; international relations